Epistemology of Al-Shifāʾ Law in Islamic Jurisprudence: Integrating Revelation-Based Healing Into Contemporary Discourse - Wakia, Nurul; Yusuf, Muhammad; Haddade, Hasyim; HR, Sabriadi (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The al-Qur'an, as the word of God (kalāmullāh), has various multidimensional functions for Muslims, one of which is as a healer (al-Shifa'), for both spiritual and physical ailments. In a spiritual context, the al-Qur'an cures ailments of the heart such as misguidance, doubt, and ignorance; while in the physical aspect, the al-Qur'an serves as a means of healing through the practice of ruqyah syar'iyyah. This article aimed to examine the meaning of al-Shifa' using the thematic exegesis method (tafsīr mawḍūʿī), compile related verses, and examine the views of classical exegetes such as Ibn Kathīr and al-Rāzī, as well as contemporary exegetes such as Quraish Shihab and Wahbah al-Zuḥailī. This study also highlighted the practical implementation of the concept of al-Shifa' in the lives of Muslims, particularly in the spiritual realm and al-Quran-based alternative medicine. This study employed a qualitative approach with a literature review, examining primary literature in the form of al-Quran verses and Qur’anic exegesis books, as well as secondary literature in the form of articles, journals, and books related to Qur'anic healing. The results showed that the al-Quran, as a source of healing, had a holistic function: healing psychological and emotional aspects, and was used in physical treatment through ruqyah. Scholars agreed that the meaning of syifā' was not merely physical, but rather profoundly spiritual and theological. In practice, reciting certain verses from the al-Quran was believed to calm the soul, alleviate anxiety, and be part of faith therapy. The concept of al-Syifā' in the al-Quran provided an understanding that true healing came not only from medical treatment but also through spiritual closeness to God. The al-Quran presented a comprehensive solution to address the physical and spiritual crises facing modern humans.